EFEKTIVITAS PENGGUNAAN MEDIA EDMODO SEBAGAI PENUNJANG PEMBELAJARAN KIMIA - Siti Muzyanah; Henie Poerwandar Asmaningrum; Yorinda Buyang (Musamus Journal of Science Education, 2018)
This research aims to discover the effectiveness of using Edmodo’s Media as Chemistry’s learning support in SMA Plus Muhammadiyah Merauke. Type of this research is an experimental research, the type of experiment used is pre-experimental with one group pretest-posttest design. Population of this research is all students of SMA Plus Muhammadiyah Merauke consist of 70 students. Sample of this research is class X in which there are 25 students obtained by using purposive sampling. Data analyzing used is t-test and observation sheet. Based on the result of the research obtained the percentage of learning outcome’s completeness which is 92%, N-Gain score which is 0,68 (categorized as medium), and tcount which is 19,11 (tcount>ttable). Besides, this research’s result is strengthen by the supporting data which are the observation of teacher skill and the observation of students activities, sequentially in the percentage of 91,25% and 88% in which both categorized as very good (complete). As the conclusion, Edmodo’s Media is effective to used as chemistry’s learning support in SMA Plus Muhammadiyah Merauke. Keywords: Effectiveness, Edmodo, Chemistry